Transactional Sex as a Response to Risk in Western Kenya - Robinson, Jonathan; Yeh, Ethan (2012)
Though formal and informal sex work has long been identified as crucial for the spread of HIV/AIDS, the nature of the sex-for-money market remains poorly understood. Using a unique panel dataset constructed from 192 self-reported diaries, we find that women who engage in transactional sex substantially increase their supply of risky, better compensated sex to cope with unexpected health shocks, particularly the illness of another household member. These behavioral responses entail significant health risks for these women and their partners, and suggest that these women are unable to cope with risk through other consumption smoothing mechanisms.